A mild and efficient Zn-catalyzed C-glycosylation: synthesis of C(2)–C(3) unsaturated C-linked glycopyranosides1. Issue 36 (23rd April 2015) - Reddy, Thurpu Raghavender; Rao, Dodla Sivanageswara; Kashyap, Sudhir
<x xml:space="preserve">Abstract</x> A mild and efficient protocol for the C-glycosylation from glycals is described by using Zn-catalysis.